Population Decline for Plants in the California Floristic Province: Does Demography or Geography Determine Climate Change Vulnerability? - Backus, Gregory A. (2025)
Aim: The role of species' demography and geography can be difficult to disentangle when projecting future population decline under global change. By constructing and combining species-specific ecological models for plants in a fire-prone Mediterranean-type ecosystem, we explored how demography and geography can differentially affect population projections of plant species in the coming century.Location: California, USA.Methods: We developed a set of linked demographic-distribution models for six Californian plant species, representing a range of life history characteristics found in the California Floristic Province. These ecological models simulate stochastic population dynamics to show how plant species might differentially respond to geographic patterns in climate change and fire regime scenarios when considering species-specific traits. By integrating each combination of species-specific demographic model with each of the other species' distribution models, we assessed the role of habitat loss and demographic constraints in the population declines of these plants.Results: We found that all species experienced substantial population decline by 2085 under our simulations, with total species' abundances primarily influenced by habitat loss from climate and land-use change. Species' demography had a larger influence on subpopulation-level dynamics, especially in areas predicted to have frequent wildfires.Main Conclusions: Our research underscores that responses to climate change are shaped by the interplay between species-specific demography and geographic distribution. Though species distribution models may be able to predict changes in which areas will be suitable throughout species' theoretical niche limits, species-specific population dynamics are critical to projecting how populations might change in abundance at more local scales. Conservation decisions should integrate both geographic and demographic factors to effectively address climate-induced threats at both regional and local scales.